Teachers’ professional identity measures in the Kingdom of Saudi Arabia from the perspective of Rasch Model Framework - Abdullah J, AlghamdiHamad; Samsudin, Mohd Ali; Abdul Rahim, ShamimahParveen; H. Alqarni, Mohammed Ali; Ismail, Mohd Erfy (2021)
This study aims to assess the psychometric properties of the professional identity measure of the professional identity of Mathematics teachers in the Kingdom of Saudi Arabia. Professional identity topic has not been widely addressed in the Arab environment. Studying the Mathematics Teachers’ Professional Identity (TPI) is important because only few and inadequate body of research has been performed in the Arab environment. Establishing measuring tool on the TPI contributes on the evaluation of the teachers in Kingdom of Saudi Arabia and their roles in the educational process in the country. This study applies descriptive approach. 600 secondary Mathematics teachers were involved. The adapted version of the questionnaire designed by Albaqi'i (2014) used to measure the Mathematics TPI. Delphi techniques in three rounds to gather experts’ opinion about the suitability of Mathematics TPI questionnaire used in the Kingdom of Saudi Arabia context. Rasch model as a framework applied to assess the psychometric properties of Mathematic TPI questionnaire. The results are valuable in terms of analyzing the psychometric properties for the first version of Mathematics TPI, to improve Differential Item Functioning (DIF) and the psychometric properties for the revised version of Mathematics TPI Questionnaire.